2015
DOI: 10.1128/aem.00823-15
|View full text |Cite
|
Sign up to set email alerts
|

A Putative Type III Secretion System Effector Encoded by the MA20_12780 Gene in Bradyrhizobium japonicum Is-34 Causes Incompatibility with Rj 4 Genotype Soybeans

Abstract: eThe nodulation of Bradyrhizobium japonicum Is-34 is restricted by Rj 4 genotype soybeans (Glycine max). To identify the genes responsible for this incompatibility, Tn5 mutants of B. japonicum Is-34 that were able to overcome this nodulation restriction were obtained. Analysis of the Tn5 mutants revealed that Tn5 was inserted into a region containing the MA20_12780 gene. In addition, direct disruption of this gene using marker exchange overcame the nodulation restriction by Rj 4 genotype soybeans. The MA20_127… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 36 publications
1
24
0
1
Order By: Relevance
“…The Type III secretion system (T3SS) [55] can either promote or impair the establishment of symbiosis, depending on the legume host [56], and has been characterized as a host determinant for rj1, Rfg1, Rj2 and Rj4 soybean cultivars [33, 57, 58]. The dominant soybean genes Rj2 and Rj4 restrict nodulation with specific strains of Bradyrhizobium [33].…”
Section: Insights From the Genome Sequencementioning
confidence: 99%
“…The Type III secretion system (T3SS) [55] can either promote or impair the establishment of symbiosis, depending on the legume host [56], and has been characterized as a host determinant for rj1, Rfg1, Rj2 and Rj4 soybean cultivars [33, 57, 58]. The dominant soybean genes Rj2 and Rj4 restrict nodulation with specific strains of Bradyrhizobium [33].…”
Section: Insights From the Genome Sequencementioning
confidence: 99%
“…The C-terminal regions of the BEL2_5 (USDA61) and MA20_12780 (Is-34) proteins are related to NopD (Figure 1B) and thus are predicted to possess SUMO protease activity. Mutant strains lacking these proteins gained the ability to induce nodules on Rj4/Rj4 soybeans, suggesting that NopD family proteins possess asymbiotic effector activity on soybean genotypes expressing Rj4 (Faruque et al, 2015;Tsurumaru et al, 2015;Yasuda et al, 2016). Rj4 encodes a specific thaumatin-like protein that only differs in few amino acids from homologs (Tang et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Although several studies have reported mapping nodulation‐related traits or biological nitrogen fixation traits in legumes, the candidate genes that are most likely involved in symbiotic nodulation have not been studied (Diaz et al., ; Heilig et al., ; Kamfwa et al., ). The candidate genes for nodule‐related QTLs that were confirmed and cloned were Rfg1 , Rj2 and Rj4 (Tang et al., ; Tsurumaru et al., ), which were a variety of dominant genes shown to restrict nodulation in soybean, especially by Brandyrhizobium (Sugawara et al., ; Tang et al., ). However, mining candidate genes by QTL mapping involved in symbiosis signal pathway transmission for revealing symbiotic mechanisms was also considerable and efficient.…”
Section: Discussionmentioning
confidence: 99%